Does depression correlate with elderly patient satisfaction andperceived quality of hospital care? - Raftopoulos, Vasilios (My University, 2003)
Patient satisfaction with quality of hospital care is a dominant concept with respect to the implementation of quality assurance and quality improvement programs. Elderly patients are the central users of health care services and therefore the assessment of elderly perceived quality of hospital care is important for strategy planning and evaluation of health care services. The relevance of patient satisfaction studies is often questioned because of conceptual and methodological problems due to the underused qualitative research. The aim of this research was to develop global scales that, in comparison with existing patient satisfaction scales would: (1) be valid and reliable, assessing elderly patients' satisfaction with quality of hospital care, based on the existing literature evidence, on results of a qualitative research and on a previous developed conceptual framework, (2) measure perceived quality of hospital care from the perspective of elderly patients and (3) explore how elderly patients' depression (by using Geriatric Depression Scale) correlates with patient satisfaction and perceived quality of hospital care.
Keywords: Patient satisfaction; Hospital health care; Older people--Hospital care; Depression in old age; Open access publishing